Analisis Times Interest Earned Ratio, Net Profit Margin, Current Ratio Terhadap Return Saham - LA Syara Alayya; R. Deni Muhammad Danial; Dicky Jhoansyah (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
Based on the results of the research it was found that the Stock Return variable has decreased in the Property and Real Estate Subsector in 2020-2020. With the decline in stock returns caused by stock prices in this sub-sector experienced a decrease in stock returns which will have an impact on the capital market. The decline in the share price of the Property and Real Estate company was due to investors not wanting to invest their capital in the company because the company experienced a decline in sales. This study aims to determine the analysis of Times Interest Earned Ratio (TIER), Net Profit Margin (NPM) and Current Ratio (CR) on Stock Returns (Studies on Property and Real Estate Companies Listed on the Indonesia Stock Exchange for the 2020-2022 period). The method used in this research is descriptive and associative with a quantitative approach. The sample used is the Property and Real Estate Subsector with a population of 30 using the natural setting technique with multiple linear regression data analysis techniques, multiple correlation coefficients, coefficient of determination, and to test the research model using the F-Test and for testing the hypothesis using the T-Test with using the SPSS 24 software application. The results of this study showed that there was a significant influence on the variable Times Interest Earned Ratio on Stock Return with the results Fcount 4,861 > F table 2.975 and the results of research on testing the T-Test Hypothesis on the variable Times Interest Earned Ratio (X1) to Variable Return stock (Y) there is a significant influence on Stock Return (Y).